2020
DOI: 10.1155/2020/4814378
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Distress in Young Adults with Type 2 Diabetes: A Cross-Sectional Survey in China

Abstract: Background. Diabetes distress is a negative emotion related to diabetes management, which can compromise self-care and management of diabetes. However, few studies on diabetes distress have focused on young adults with type 2 diabetes in China. Methods. A cross-sectional survey was conducted. Using a convenient sampling method, 98 young adults with type 2 diabetes who were admitted to our hospital from June 2017 to July 2018 were selected as research subjects. They were investigated using a basic demographic q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
5
13
0
6
Order By: Relevance
“…This finding was consistent with the results of prior studies. 39 , 47 , 48 However, some studies have found no association between having diabetic complications and DRD. 13 , 20 , 49 In contrast to previous studies, lower education level was a major factor for high diabetes distress scores in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with the results of prior studies. 39 , 47 , 48 However, some studies have found no association between having diabetic complications and DRD. 13 , 20 , 49 In contrast to previous studies, lower education level was a major factor for high diabetes distress scores in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…У 2005 році була розроблена спеціалізована шкала дослідження діабетичного дистресу (Diabetes Distress Scale, DDS), надійність та валідність якої знайшли підтвердження в багатьох роботах [23][24][25][26][27][28][29][30][31][32][33]. З методом дослідження дистресу при ЦД за шкалою DDS, який широко використовується у всьому світі, можна ознайомитися на сайтах https://diabetesdistress.…”
Section: оглядиunclassified
“…Проведене в Китаї обстеження 98 госпіталізованих молодих хворих на ЦД2 виявило діабетичний дистрес, у розвитку якого важливу роль відіграли переживання, пов'язані з режимом, емоційними навантаженнями та міжособистісними відносинами [32]. Результати п'ятидесяти п'яти досліджень із залученням 36 998 осіб встановили наявність діабетичного дистресу в 36% хворих на ЦД2, який був значно виразнішим у хворих із депресивними симптомами та в жінок [31].…”
Section: оглядиunclassified
“…A systematic review found that the overall global prevalence of DD was 36.0% in patients with T2D [ 5 ]. A study also showed that approximately 42.5%–77.2% of Chinese people with T2D experienced DD [ 6 ]. DD is a negative emotional response that includes worries, fears, and frustrations caused by the perceived burden from living with and managing diabetes on a daily basis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, the DDS17 was first translated by Yang and Liu in 2010 [ 16 ]. The Cronbach’s α coefficient of the Chinese DD Scale ranged from 0.84 to 0.95 [ 6 ]. Although it demonstrated good psychometric properties and has been used in observational and experimental studies for several years, the language accuracy and understandability still had room for improvement.…”
Section: Introductionmentioning
confidence: 99%